Kajian Elemen Arsitektur Vernakular pada Pendopo Agung Trowulan dengan Studi Bentuk dan Ruang - Agriya, Bulan Surya; Koeswanto, Alfinto Deonova; Murti, Farida; Tohar, Ibrahim (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
As a form of cultural heritage in Indonesia, Pendopo Agung Trowulan is located in the Trowulan archaeological site which has extraordinary historical value and is an important representation of traditional Javanese architecture. This study aims to identify the main characteristics of vernacular architectural elements integrated in the building's design, as well as analyze the vernacular architectural elements that influence the building's form and space. The method used was descriptive qualitative involving literature review, field observations, and interviews with local residents. The analysis was focused on various physical aspects such as the form and space in the Trowulan Great Hall building. With all its functions and meanings, Pendopo Agung Trowulan is a clear evidence of how vernacular architecture can play an important role in preserving and promoting local wisdom and enriching the social and cultural life of the community.